Survival Trends, Determinants of Mortality, and the Impact of Advance Directives: An Observational Study from the Pakistan Registry of Intensive Care - Islam, Fahad; Ansari, Muhammad Imran; Taimoor, Lalarukh; Lashari, Naveed Aslam; Arif, Muhammad Sohaib; Baig, Mirza Yousuf; Umair, Madiha; Abubaker, Jawed (Pakistan Armed Forces Medical Journal, 2026)
Objective: This study assesses survival trends and identifies determinants of adverse outcomes (at hospital discharge and 90-day) among ICU patients, for the whole cohort and in the context of advanced directives (AD). Study Design: Correlational Study. Place and Duration of Study: Pakistan Registry of Intensive Care (PRICE), National Institute of Cardiovascular Diseases (NICVD) in Karachi, Pakistan, between Jan 22 and Dec 23. Methodology: Data for a total of 1570 patients were analyzed from the PRICE registry. We included patients of either gender, aged≥ 18 years, who were admitted to the ICU. Patients who deferred consent for participation in the PRICE registry were excluded. Data included clinical and laboratory parameters at ICU admission, treatment details, AD, ICU, and hospital discharge outcomes, and 90-day post-discharge survival. Results: Of the 1570 patients (mean age 57.6±14.3 years, 945 males), 83.3% required mechanical ventilation (MV), 76.7% needed vasoactive therapy, 2.9% underwent renal replacement therapy, and 34.9% received antibiotics. ICU mortality was 16.6%, and 20.4% died by hospital discharge. At 90 days post-discharge, follow-up was successful for 59.1% of patients, with a 20.6% mortality rate. Among 436 DNR patients, 41.1% died in-hospital. DNR status raised in-hospital and 90-day mortality risks (OR: 4.91, 3.48). Conclusion: High ICU and hospital mortality rates underscore the challenges in managing critically ill patients, particularly those on MV. The study calls for a culturally sensitive approach to ICU management, emphasizing AD, early risk factor identification, and individualized patient care strategies.